Die geländeklimatische Bedeutung des Bergschattens und der Exposition für das Gefüge der Natur- und Kulturlandschaft - Böhm, Hans (ERDKUNDE, 1966)
Taking as a starting point the studies of K. Peucker (1897), F. Huttenlocher (1923), A. Garnett (1935, 1937) and others, the paper attempts to evaluate the importance of mountain shadow for the differentiation of the cultural landscape within high mountains. In addition to the factors latitude, altitude, aspect and degree of slope, which normally determine the total amount of potential insolation per unit area, there is in high mountains the mountain shadow which is particularly extensive in west-east running valleys. Adapting A. Garnett’s method, a shadow map of an Alpine valley (Paznaun valley, Tirol) on a scale of 1 : 50,000 was constructed by graphical means. It shows for this south-west north-east running valley the number of days of the year when valley flanks or parts thereof lie in mountain shadow at 12 noon. In order to ascertain the diurnal and annual course of increase and decrease of the shadow, measurements of duration of insolation and shadow conditions were carried out with F. Tonne’s horizontoscope at over a hundred spots simultaneously with agricultural mapping. For each of these a shadow diagram (skioisopleth-diagram) was constructed and the diagrams arranged into nine types according to the following criteria: 1) Duration of time in the shadow during the day 2) Duration of shadow conditions on mornings and afternoons respectively and the relationship of these two to each other. Taking as example the Paznaun valley and by evaluating existing literature on this topic, the following general regular consequences of mountain shadow were found: In low altitudes where there is little difference between air and ground temperature the influence of mountain shadow is small. In higher altitudes where the difference between air and ground temperature is more pronounced mountain shadow plays an important role in the structure of the cultural landscape though this declines again above the climatic limit of arable cultivation. In a very general way one may state that the degree of contrast between adret and ubac increases with increasing altitude.